Children and energy-dense foods – parents, peers, acceptability or advertising?. (12th September 2017) - Tarabashkina, Liudmila; Quester, Pascale G.; Crouch, Roberta
Abstract : Purpose: Studies to date have focused on one or very few factors, rather than exploring a host of influences associated with children's consumption of energy-dense foods. This is surprising as multiple agents are relevant to children's food consumer socialisation (parents, peers, social norms and food advertising). This study aims to address these gaps and offers the first comprehensive empirical assessment of a wide cluster of variables. Design/methodology/approach: A cross-sectional study was undertaken with children aged 7-13 years and their parents/main carers, collecting family metrics from parents and data directly from children. Structural Equation Modelling was used to estimate a series of interdependence relationships in four steps, revealing the increased explained variance in children's consumption of energy-dense foods. Findings: The inclusion of multiple potential factors increased the percentage of explained variance in children's consumption of energy-dense foods. The models explicate which factors relate to frequent consumption in children, and clarify various indirect influences on children through parents. Originality/value: For the first time, a wider range of variables was integrated to maximise the percentage of explained variance in children's behaviour, providing policy makers and social marketers with novel insights regarding areas that need to be prioritised for consumer education. Both direct and indirect relationships were assessed. Data were collected from parents and their children to provide an original methodological contribution and richer data for investigation.